Application of Barracuda Fish Skin Gelatin (Sphyraena barracuda) on Characteristics of Liquid Smoke Flavored Ice Cream - Sitoresmi, Riris; Swastawati, Fronthea; Suharto, Slamet (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Gelatin can be applied to ice cream as a stabilizer. The flavors of ice cream on the market only focus on ordinary flavors such as chocolate, vanilla, and strawberry. Liquid smoke as a flavoring in ice cream can be used as an innovation. The purpose of this study was to determine the best concentration of liquid smoke in ice cream and determine the effect of adding gelatin with different concentrations on the physical quality of ice cream. The treatments used were liquid smoke with different concentrations (0%, 0.3%, 0.5%, and 0.7%) in the opening study and gelatin concentrations of 0%, 0.2%, 0.4%, and 0.6% in the main study with three repetition times. Parameters observed were hedonic, overrun, melting time, pH, and viscosity. The analysis showed that all test treatments had a significant effect (P<0.05). Adding liquid smoke with a concentration of 0,7% was the best treatment, with a hedonic value of 7.97<µ<8.17 (preferred by the panelists). The best treatment results for barracuda fish skin gelatin on the characteristics of ice cream were at a concentration of 0,4% with overrun results of 62,67% ± 0,58, melting speed 31.37±0.95 minutes, pH 6.33±0.02, viscosity of 2567.67±142.38 cP and hedonic value of 7.61 <µ <7.79 (preferred by the panelists).